Optimalisasi Teknologi IOTAIDA dalam Budidaya Sayuran Genjer untuk Menunjang Wirausaha Masyarakat Ulugabe - Emmi Juwita Siregar; Bismi Robbuddin; Riski Waruwu; Defayanti Anatasya; Amanda Lupita; Zulfahmi Pasaribu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This socialization aims to develop the potential to see business opportunities and increase work effectiveness in understanding Genjer cultivation and ease of marketing using AIDA IoT technology in the Ulugabe village community. The problems studied are 1) How is the quality of the Genjer plant condition in the Ulugabe village community? 2) How does the community handle Genjer cultivation in Ulugabe Village? 3) How does the community manage Genjer plants to marketing? The research method used is introducing socialization with a Plant Science and IoT Technology approach. Where data collection is carried out through observation, presentation and documentation studies. The results of the observation stated that the level of understanding of Plant Science and Genjer plant processing as a business still needs to be improved, especially in marketing techniques that can be more efficient using AI technology. Increasing the use of AI software technology such as Chat Bot examples is still not optimal among the community, including teenagers. Therefore, the ability of the community to use and understand it still needs to be improved, especially in the form of Genjer plant cultivation applications and the application of IoT technology to master agricultural technology. The socialization of this research resulted in a thought design to see the genjer plant as a business opportunity with ease in the application of IoT technology which is expected to increase productivity, quality of entrepreneurship, and application of science in the Ulugabe village community.